What is wrong with the medical literature?. (2nd January 2017) - Bell, R. J.
Abstract: Young clinicians are encouraged to carry out and publish research, often without adequate research training or supervision. At best, the publication of poor-quality studies contributes noise to the literature; however, some published findings will be false and potentially misleading. If we are serious about improving the quality of the medical literature, we need to make some systemic changes to the current drivers of publication including improving peer review, having a system of post-publication feedback, promoting the publication of research protocols and data sets, making funding available for the replication of research studies, and changing how we assess a researcher's publication record. We also need to improve the research training and supervision of young clinical researchers.